Studies on the Effects of Benz [a] Anthracene and Benzo [ghi] Perylene on the Lung of Rats - Movassagh, Sanaz (2003)
Air pollution or haze contains a variety of detrimental agents including benz[a]anthracene (BA) and benzo[ghi]perylene (B[ghi]P). These carcinogenic compounds which are found during the Malaysian haze episodes affected on health and economic status of nation. In view of developing strategies and bringing about a remission of noxious haze effects in humans, acute and chronic exposure to BA, B[ghi]P and their combination was studied in rats. The acute exposure studies was conducted to evaluate apoptosis in the lung of rats following treatment with BA, B[ghi]P and BA+B[ghi]P. Rats not receiving any treatment served as control while those administered with BA, B[ghi]P and BA+B[ghi]P were instilled intratracheally at the dose of 8 ng (4 ul), 16 ng (8 ul) and 12 ng (6 ul) respectively. Animals in treated groups were euthanised at 1, 4, 8, 16 and 24 hours postinstillation (p.i.) and rats from the control group were only killed 24 hours p .i . Apoptosis assessment was made on haematoxylin-eosin stained histologic sections, terminal deoxynuc1eotidyl transferase-mediated dUTP nick-end labeling (TUNEL) analysis and DNA laddering of trachea and lung samples. Different stages of apoptosis were found in the pneumocyte and bronchial epithelium of all treated rats euthanised at the respective time post-instillation and the percentage of apoptotic cells increased with advancement of time, especially in 16 and 24 hours p.i. which was the highest for each group (P<0.05). This was also confirmed by TUNEL analysis and DNA laddering. The chronic exposure studies was conducted on changes in the lung of BA, B[ghi]P and BA+B[ghi]P-induced rats during a three month period encompassing gross and histopathologic findings, immune response, levels of marker enzyme and the effect of raw garlic as an anti-tumour factor. Rats from the control, BA, B[ghi]P and BA+B[ghi]P group were daily fed on a commercial basal diet while rats from the garlic (G), [BA+G], [B[ghi]P+G] and [BA+B[ghi]P+G] group were fed the basal ration containing garlic incorporated at the rate equivalent to an intake of 80 mg/kg body-weight/rat/day. The results showed growth disturbances in pneumocytes and bronchial epithelium of rats from the BA, B[ghi]P and BA+B[ghi]P groups. Apoptosis was also detected in these groups. In addition, rats treated with BA+B[ghi]P had the lowest levels of IgA, IgG, alveolar macrophages activities and glutathione S-transferase in the lung. In conclusion, environmental hazard of BA, B[ghi]P and their combination to lungs of rats as target organs causes deleterious changes either by short or long term exposures and garlic has a great potential in alleviating the chronic effects.